Yield line analysis of two way reinforced concrete slabs having two adjacent edges discontinuous with opening part I : derivations - Kumar, Veerendra; Bandyopadhyay, Milan (Journal of Structural Engineering, 2025)
Reinforced concrete rectangular slab for two adjacent edges discontinuous with opening at different locations have been analysed using yield line theory. The ratios of the corresponding lengths of the sides of the opening and the slab are kept the same and the size of opening up to half of the length of the slab sides are considered. The ratio of the span moments to support moments is kept equal to 0.75. The design tables and the examples to explain the use of the tables for analysis of slab will be presented in Part II.